A arte e seu ensino no Brasil : tendências e perspectivas a partir do GT 24 da ANPED - Bedin, Thaís (2015)
This research focuses on the scientific production trends on the Art and its Education in Brazil, using as source the Working Group 24 of ANPED (GT24), entitled Education and Art, observing the time snip from 2009 to 2012. In the investigative process, it is been analyzed the Art Education trajectory and the academic and scientific production in this working group and it is realized the diagnosis of the themes of the Art and its teaching, noting the proposals for the period. The work includes the concern of the increase of number of research focused on these areas, in various levels of formal education, as well as the need of building a survey of what has been produced on this issue on the national stage, allowing the enjoyment of the presented results in favor of teacher education. In its methodological approach, this study is guided by the contributions of documentary and bibliographical research, taking a corpus of 59 articles published in the GT 24 of Anped on the period in question, apostrophizing them with several questions, such as: who is producing in this area of Knowledge (gender, formation, institutions)? What are the gaps and weaknesses of this investigative field? What are the advances displayed in this production? The text presented approaches the art ways and of its teaching, identifying scenarios, trends and prospects of this production, approaching studies called "knowledge state". All considerations made possible the construction of a panorama that points as gaps the lack of questioning for the curriculum and the role of the Art teacher. In the same way that it identifies the fragility of works for specifically the treatment of Art tools, of evaluation, of art and their views learning. Also, as improvements, it stands the appropriation of Information and Communication Technologies as tools for the teaching of Art, the expansion of the discussions on the theme of Urban Art and of Art in childhood and, also, the marked boundary from one space to discussions focused on the issues and body image